RUMUSAN OPERASIONAL VISI, MISI DAN TUJUAN DALAM SISTEM ORGANISASI PENDIDIKAN ISLAM - Putri Dewi Stefany; Risalatul Lailiya; Mardiyah (Program Studi Manajemen Pendidikan Islam, 2025)
Vision and mission are crucial elements in the management of Islamic educational institutions that function as a guide in setting goals and developing strategies. Vision is defined as a picture of an ideal future, oriented to the achievement of the pleasure of Allah SWT, and covering aspects of life in this world and the hereafter. Mission, as a concrete effort to realize the vision, explains the methods that must be used by the institution to achieve the goals that have been set. In the process of formulating the vision and mission, it is important to involve all stakeholders in education in order to create a common agreement and commitment. However, formulating a vision and mission is not without challenges, including differences of views regarding Islamic teachings and the needs of the rapidly changing times. This article will discuss the importance of the vision and mission in the context of Islamic education, the challenges faced in its formulation, and strategies that can be implemented to deal with today's educational needs. Through a deep understanding, it is hoped that Islamic educational institutions can produce a generation that is competent, responsible, and able to face world challenges while adhering to Islamic values